Food items of Macrotus waterhousii (Chiroptera: Phyllostomidae) in central Mexico - Sánchez, Oscar; Wilson, Don E. (THERYA, 2016)
Macrotus waterhousii is a phyllostomid bat whose diet is poorly known, particularly in semiarid and temperate central Mexico. In this work additional information is reported from food remains discarded by this bat, including taxonomic composition, frequencies and size range of consumed insects; the assessment of a prediction on prey hardness of food insects, at the ordinal level; relative energy reward of insect prey in the sample; a comparison of the composition of the food sample from the arid study locality against one from a subtropical-temperate site; and brief comments on the known ecological importance of particular prey in the arid site. A sample of insect food remains discarded by Macrotus waterhousii bulleri, was recovered from under a roost in semiarid northern Querétaro, Mexico. The taxonomic identity, estimated relative abundance, size, hardness, and ecological relations of prey species in the sample were studied and results were compared with reference to feeding ecology. A comparison of the data with available information on food taken by Macrotus waterhousii mexicanus in temperate-subtropical central Mexico was made. Information on the importance of the most relevant identified insects was extracted from literature and analyzed. In Querétaro, Lepidoptera, Hymenoptera, and Coleoptera were frequent; moths dominated but, as a single species, the (winged) ant, Atta mexicana was most frequent. Nocturnal insects were frequent; diurnal ones may have been gleaned at night. A sample from Estado de México featured Orthoptera, Coleoptera, and Lepidoptera. Wingspan range of frequent prey in Querétaro was 25-80 mm, but moths over 70 mm were over one fifth of the sample. Prey hardness estimation was similar to that for Macrotus californicus. Some insects identified are of ecologic and agricultural relevance. Insects known to be seasonally abundant in the environment were also abundant in the sample, presumably captured according to that availability. However this bat, aside from eating insects of moderate size in proportion to its jaw size, is also capable of capturing large moths and these may represent a significant energy intake. Most insects are nocturnal species. The taxonomic composition of the food samples from both areas suggests that M. waterhousii (sensu lato) may be mostly an opportunistic predator. Local insect fauna composition and dynamics may be hypothesized to influence food taken by M. waterhousii. Several insect species consumed by this bat in semiarid Querétaro have crucial roles in the ecology of arid land vegetation, as well as some economic importance for agriculture as pests.